NEW PERMIAN ECHINODERMS FROM NORTHEASTERN OMAN HAVE CONNECTIONS WITH TETHYAN ECHINODERM FAUNAS FROM WEST TIMOR, WESTERN AUSTRALIA, AND RUSSIA (RIVISTA ITALIANA DI PALEONTOLOGIA E STRATIGRAFIA, 2025)
Permian blastoids and crinoids are described from the Batain region in northeastern Oman. New collections are from the Qarari Unit and are dated as late Kungurian to early Roadian. Six blastoid species assigned to three genera, 15 species-level crinoids assigned to 14 genera (some with question), and several crinoid taxa left in open nomenclature are described. New taxa include Angioblastus qararii sp. nov.; A. omanensis sp. nov.; Deltoblastus sevastopuloi sp. nov.; Disgregacrinus aridus gen. nov., sp. nov.; Eoindocrinus ageri sp. nov.; E. spinosus sp. nov.; Jaramahcrinus warlichi gen. nov., sp. nov.; Proindocrinus riesae sp. nov.; Qararicrinus batainensis gen. nov., sp. nov.; Roemerocrinus? aridus sp. nov., and Synbathocrinus shackletoni sp. nov. Also, Platycrinites omanensis Webster & Sevastopulo, 2007 is reassigned to Pleurocrinus, and Calycocrinus conicus is recognized as a species. At the genus level, the Oman echinoderms are associated with Permian faunas in Australia, Russia, and West Timor; however, at the species level, the fauna is largely endemic to Oman. The occurrence of Timoroblastus is the first verifiable report of this genus outside of Timor.
Keywords: Permian; Echinodermata; Crinoidea; Blastoidea; Oman; Timor.